IATROGENIC INJURIES DURING CENTRAL LINE PROCEDURES AND RELATED MEDICO-LEGAL ISSUES: A CASE SERIES OF FOUR CASES (Journal of Forensic Medicine & Toxicology, 2025)
A central venous line is frequently placed for a number of reasons in various therapeutic contexts. Central lines come with a number of risks, and the procedure can lead to several complications. The nature of complications varies depending on the kind of central venous access and might manifest either immediately or later on. Iatrogenic injuries associated with central venous access can lead to significant morbidity and mortality. These injuries are medico-legally very important, as they may cause the wrong interpretation by an inexperienced autopsy surgeon due to artefacts. Artefacts as a result of iatrogenic injuries in the form of diffuse effusion along neck muscles may be interpreted as neck compression by blunt force. Wrong technique during the procedure of central line may lead to fatal injuries due to guide wire or puncture needle insertion. Such iatrogenic injuries causing death may be grounds for a charge of medical negligence against treating doctors. This article discusses four cases of iatrogenic injuries due to the central line and its relevant medico-legal aspects.
Keywords: Central line; complication; pneumothorax; guide wire; artefact; neck compression